Markers of endothelial cell activation and neutrophil extracellular traps are elevated in immune thrombocytopenia but are not enhanced by thrombopoietin receptor agonists. Issue 185 (January 2020) - Garabet, Lamya; Henriksson, Carola E.; Lozano, María Luisa; Ghanima, Waleed; Bussel, James; Brodin, Ellen; Fernández-Pérez, María Piedad; Martínez, Constantino; González-Conejero, Rocío; Mowinckel, Marie-Christine; Sandset, Per Morten
Abstract: Introduction: Patients with immune thrombocytopenia (ITP) are at increased risk of thrombosis, which seems to be further enhanced by treatment with thrombopoietin-receptor-agonists (TPO-RAs). The underlying mechanisms of thrombosis in ITP are not fully understood. Endothelial cell activation and neutrophil extracellular traps (NETs) play important roles in thrombosis, however, their roles in ITP itself, or in TPO-RA-treatment, have not yet been fully explored. We aimed to investigate whether endothelial cell activation and NETs are involved in the hypercoagulable state of ITP, and whether TPO-RA-treatment enhances endothelial cell activation and NET formation. Material and methods: We measured markers of endothelial cell activation including intercellular adhesion molecule-1 (ICAM-1), vascular adhesion molecule-1 (VCAM-1) and thrombomodulin in 21 ITP patients, and E-selectin in 18 ITP patients. Markers of NET formation, citrullinated histone H3-DNA (H3Cit-DNA) and cell-free DNA (cfDNA), were measured in 15 ITP patients. All markers were measured before, and 2 and 6 weeks after initiation of TPO-RA-treatment in ITP patients, and in matched controls. Results: Higher levels of ICAM-1, thrombomodulin, and H3Cit-DNA were found in ITP patients, both before and after TPO-RA-treatment, compared with controls. No differences were found for VCAM-1, E-selectin or cfDNA. TPO-RA-treatment did not further increase markers of endothelial cell activation or NET formation. Conclusions: This study showed that ITP patients have increased endothelial cell activation and NET formation, both of which may contribute to the intrinsic hypercoagulable state of ITP. TPO-RA-treatment, however, did not further increase endothelial cell activation or NET formation indicating that other drug-associated prothrombotic mechanisms are involved. Highlights: ITP patients have higher ICAM-1 and thrombomodulin than controls suggesting increased endothelial cell activation/injury. ITP patients have higher NET marker H3Cit-DNA than controls indicating increased NET formation in these patients. Treatment with TPO-RAs does not enhance endothelial cell activation or NET formation.